2017
DOI: 10.1016/j.jpeds.2017.02.060
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Effort of Breathing for Infants on Nasal Modes of Respiratory Support

Abstract: Objective To directly compare effort of breathing between high flow nasal cannula (HFNC), nasal intermittent mechanical ventilation (NIMV), and nasal continuous positive airway pressure (NCPAP). Study design This was a single center prospective cross-over study for patients <6 months in the cardiothoracic or pediatric intensive care unit receiving nasal noninvasive respiratory support after extubation. We measured effort of breathing using esophageal manometry with pressure-rate product (PRP) on all 3 modes.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 33 publications
0
5
1
Order By: Relevance
“…The strongest evidence for NIMV in the pediatric population to date are limited to pathologies encountered in the NICU; for example, it shows significant clinical benefit over other modes of NIV in neonatal respiratory distress syndrome, apnea of prematurity, and the prevention of post-extubation failure[ 4 , 12 , 13 ]. In discordance with the NICU literature, a recent prospective study of NIV for post-extubation support in the PICU showed no difference in respiratory effort when compared between NIMV, HFNC, and CPAP, though NIMV in this study was synchronized to approximately 50%[ 14 ].…”
Section: Discussioncontrasting
confidence: 58%
“…The strongest evidence for NIMV in the pediatric population to date are limited to pathologies encountered in the NICU; for example, it shows significant clinical benefit over other modes of NIV in neonatal respiratory distress syndrome, apnea of prematurity, and the prevention of post-extubation failure[ 4 , 12 , 13 ]. In discordance with the NICU literature, a recent prospective study of NIV for post-extubation support in the PICU showed no difference in respiratory effort when compared between NIMV, HFNC, and CPAP, though NIMV in this study was synchronized to approximately 50%[ 14 ].…”
Section: Discussioncontrasting
confidence: 58%
“…Finally, given our study inclusion and exclusion criteria, we cannot generalize our findings to other clinical scenarios where NIV is used, such as the cardiac ICU population or for prevention of extubation failure. 4,17 The study setting was a quaternary pediatric referral center our findings may not be generalizable to community hospitals with varying degrees of respiratory services.…”
Section: Discussionmentioning
confidence: 98%
“…1 A spectrum of respiratory support modalities has emerged, ranging from oxygen delivery devices such as heated humidified high-flow nasal cannula (HFNC) to NIV modalities such as continuous positive airway pressure (CPAP) and bilevel pressure positive pressure ventilation (BiPAP). 2 These modalities reduce work of breathing by inspired gas conditioning and reduced airway resistance, [2][3][4][5][6][7][8][9][10][11] with BiPAP enhancing carbon dioxide clearance. 12 Since the introduction and wide application of these modalities, a reduction in intubation rates has been observed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This range of PRP corresponds to a pressure-time product range between 75 and 200. In addition, we have also found this range is significantly lower than the typical PRP range for infants with bronchiolitis who are maintained on high flow nasal cannula (> 75% have PRP over 400), and slightly lower than the typical PRP range for infants on nasal Continuous Positive Airway Pressure (CPAP) [46,47]. Therefore, this range appears to result in effort of breathing even lower than what most critical care clinicians would deem acceptable for critically ill children who are not on MV.…”
Section: Acute Phasementioning
confidence: 76%